The sacrality of the secular : postmodern philosophy of religion - Onishi, Bradley B. (Columbia University Press, 2018)
Through a bold and historically rooted vision for the future of philosophy of religion, The sacrality of the secular maps new and compelling possibilities for a nonsecularist secularity. In recent decades, philosophers in the continental tradition have taken a notable interest in the return of religion, a departure from the supposed hegemony of the secular age that began with the Enlightenment. At the same time, anthropologists and sociologists have begun to reject the once-dominant secularization thesis, which both prescribed and described the demise of religion in modern societies.